Cohesive fracture in composite systems: experimental setup and first results - Valentino Paolo Berardi; Michele Perrella; Gabriele Cricrì (Fracture and Structural Integrity)
Composite systems are widely used in many engineering applications for new structures and strengthening of existing ones. Within the structural rehabilitation of civil constructions, the plating technique of beams with Fiber Reinforced Polymer (FRP) represents a quick and optimal intervention with respect to traditional ones. The failure of these composite systems usually occurs due to the FRP debonding, which corresponds to a mode II fracture of concrete specimens. In this paper, a new experimental setup for investigating the mode II fracture behavior of FRP-concrete composite structures is presented. The test equipment consists of both conventional equipment and a non-contact optical technique, Digital Image Correlation (DIC), and the test system was realized at the Design Machine Laboratory of the University of Salerno. A preliminary test was performed and the corresponding results are shown and discussed.